Mary in the Eucharistic prayers of the Eastern and Western Church - Śmiałek, Sebastian (Studia Teologiczne Białystok Drohiczyn Łomża, 2024)
The article attempts to present figure the Mather of God on the basis of Eucharistic prayers characteristic of both the Eastern Church and the Western Church. The analysis of liturgical sources, such as the anaphors of the Eastern Church, ancient and modern Eucharistic prayers of the Roman tradition, and liturgical texts developed after the Second Vatican Council, gave a synthetic picture of the unique role played by the figure of Mary in the life of the Church.